Glutamatergic Nonpyramidal Neurons From Neocortical Layer VI and Their Comparison With Pyramidal and Spiny Stellate Neurons - Andjelic, Sofija (American Physiological Society, 2009)
The deeper part of neocortical layer VI is dominated by nonpyramidal neurons, which lack a prominent vertically ascending dendrite and predominantly establish corticocortical connections. These neurons were studied in rat neocortical slices using patch-clamp, single-cell reverse transcription–polymerase chain reaction, and biocytin labeling. The majority of these neurons expressed the vesicular glutamate transporter but not glutamic acid decarboxylase, suggesting that a high proportion of layer VI nonpyramidal neurons are glutamatergic. Indeed, they exhibited numerous dendritic spines and established asymmetrical synapses. Our sample of glutamatergic nonpyramidal neurons displayed a wide variety of somatodendritic morphologies and a subset of these cells expressed the Nurr1 mRNA, a marker for ipsilateral, but not commissural corticocortical projection neurons in layer VI. Comparison with spiny stellate and pyramidal neurons from other layers showed that glutamatergic neurons consistently exhibited a low occurrence of GABAergic interneuron markers and regular spiking firing patterns. Analysis of electrophysiological diversity using unsupervised clustering disclosed three groups of cells. Layer V pyramidal neurons were segregated into a first group, whereas a second group consisted of a subpopulation of layer VI neurons exhibiting tonic firing. A third heterogeneous cluster comprised spiny stellate, layer II/III pyramidal, and layer VI neurons exhibiting adaptive firing. The segregation of layer VI neurons in two different clusters did not correlate either with their somatodendritic morphologies or with Nurr1 expression. Our results suggest that electrophysiological similarities between neocortical glutamatergic neurons extend beyond layer positioning, somatodendritic morphology, and projection specificity.